Stroke technique in C1 canoe slalom: a simulation study - Wakeling, J. M.; Pratt, J. S.; Smiešková, S. (Sports Biomechanics, 2024)
Male C1 canoe slalom athletes traditionally used cross transitions to move their paddle to the other side of the boat and off-side strokes to paddle on their non-dominant side. Conversely, female athletes often use a switching transition and on-side strokes on their non-dominant side. The purpose of this study was to use a computer model to assess the relation between cross- or switching techniques, and the relative strength (symmetry) of non-dominant compared to dominant side strokes to race times in C1 canoe slalom. We created a forward dynamics model to predict race times using stroke forces (from an indoor ergometer), drag forces (measured on-water), and probability distributions for stroke and transition times (measured from international canoe slalom competitions). The main effects from an ANOVA (p<0.05) were (i) for a given transition number and strength symmetry the race times were faster when using cross-transitions than switch-transitions (ii) for a given strength symmetry the race times became slower as the number of switch transitions increased, but there was minimal effect of the number of cross-transitions, and (iii) the closer the strength of the strokes were between the dominant and non-dominant side (as symmetry factor approached 100 %), the faster the race times.